تأثير بعض المعاملات التجريبية في إنبات بذور السرو الفضي Cupressus arizonica L. (Latakia University Journal -Basic Sciences Series, 2017)
يهدف البحث إلى دراسة أثر معاملات مختلفة في تنشيط وزيادة نسبة إنبات السرو الفضي لاستخدام شتلاته في مشاريع التحريج, حيث تم الحصول على البذور من المخاريط الناضجة وإخضاعها لمعاملات مختلفة مع البقاء على الشاهد ثم زراعتها في مكررات ضمن أكياس بولي إيتلين مع مراقبتها وحساب مؤشرات الإنبات. أظهرت النتائج أن معاملة النقع بحمض الستريك 0.1% مع تنضيد بارد 30يوم على درجة حرارة ( 5 - 4 مْ) لبذور السرو الفضي قد أعطت أعلى نسبة إنبات 75%, تلته نسبة إنبات معاملة النقع بحمض الكبريت0.1% وهيدروكسيد الصوديوم0.1% مع تنضيد بارد 30يوم حيث أعطت على التوالي ((53%-60% ولم تكن بينهما فروق معنوية, في حين أن معاملة النقع بماء الصنبور 24h أعطت نسبة إنبات 36% ومعاملة الشاهد أعطت نسبة إنبات أدنى بالمقارنة مع باقي المعاملات الأخرى حيث أعطت فقط 9%.كما أن معاملة النقع بحمض الستريك 0.1% مع تنضيد بارد30 يوم تفوقت على باقي المعاملات في التأثير على ارتفاع النبات عند نهاية التجربة.This research aims study the effect of different treatments in activate and increase percentage of germination Cupressus arizonicaL.seeds to use plants in forestation projects, seeds were get from mature conifers, and tested by different treatments with control, then cultured within polyethylene bags many times to calculate indicators of germination. The results showed that the soaking the seeds Cupressus arizonicaL. in citric acid 0.1% with cold wet stratification for 30 days at 4-5c gave higher germination percentage 75%.The treatments of the soaking seeds in sulfuric acid0.1% and hydroxide sodium 0.1% with cold wet stratification for 30 days gave respectively 60%-53% .But superiority was not significant. Other treatments; soaking the seeds in tap water 24h with cold wet stratification for 30 days gave only 36%.But the control treatment gave lower germination percentage of all just only 9%.The treatment of soaking seeds in citric acid 0.1% with cold wet stratification for 30 days surpassed the rest of the treatments in effect on plant height at the end of the experiment.